A method for fixing and paraffin embedding tissue to retain the natural fluorescence of reporter proteins. (September 2015) - Nakagawa, Akifumi; Alt, Kate Von; Lillemoe, Keith D.; Fernández-del Castillo, Carlos; Warshaw, Andrew L.; Liss, Andrew S.
Green fluorescent protein (GFP) and its derivatives are routinely employed as surrogate markers for gene expression and lineage tracing in genetically engineered mice. Tissues from these mice are commonly formalin fixed and paraffin embedded (FFPE) for histological studies. However, this results in inactivation of the natural fluorescence of these proteins, requiring their detection by immunological techniques. Here we present an ethanol fixation protocol that allows for the direct visualization of the natural fluorescence of reporter proteins while maintaining excellent tissue histology. We demonstrate the utility of this method for visualizing green and red fluorescent proteins in a wide range of murine tissues using both cytoplasmic and membrane-localized fluorescent reporter proteins. Tissues fixed by this method also allow for immunohistochemical studies, providing a single method to visualize the natural fluorescence of reporter proteins with subsequent detection of cellular proteins.